Pemanfaatan Limbah Plastik sebagai Bahan Campuran Pembuatan Paving Block : Pengabdian - Siti Marwah; Nur Anisyah; Muhammad Joko Prastio; Emelia Emelia; Fitrria Nurohim; Melisa Fitri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community-based plastic waste management program aims to transform plastic waste into economically valuable paving block products while creating new entrepreneurial opportunities for underprivileged communities. The main target of this program is the residents of Kebon IX, Sungai Gelam, Muaro Jambi Village, where based on village data, 1,446 people, or approximately 25% of the total population of 6,112, are classified as underprivileged. The method used is Technical Assistance through training and mentoring, which is considered effective as it fosters emotional closeness, patience, and motivation among participants to improve their income. The implementation stages include preparation, execution, and reporting. The activities consist of workshops and mentoring sessions on the process of transforming plastic waste into paving blocks through several steps: plastic melting, mixing with ash, molding, pressing, cooling, and producing durable plastic paving blocks ready for use. The business feasibility analysis indicates that the paving block production from plastic waste is financially viable, with a Payback Period of 1.22 years, a positive Net Present Value (NPV) of Rp129,130,707, and a Profitability Index (PI) of 2.22. Therefore, this program not only contributes to environmental management but also enhances the economic welfare of the Sukaraja Village community.